Tingkat Kecemasan Berbicara Bahasa Arab di Kalangan Pelajar Sebuah Universitas di Jawa Tengah - Rizki Parahita Anandi (LISANIA: Journal of Arabic Education and Literature, 2017)
This study is was carried out to examine the students’ level of anxiety in speaking Arabic language. Approximately 103 Arabic language education students from a university in Central Java were selected purposively to participate in this study. The instrument used in this study was the modified and translated Foreign Language Speaking Anxiety Scale by Balemir from Huang. This questionnaire consisted of 28 items with five-point likert scale ranged from strongly disagree to strongly agree. The data was then analysed using Winstep version 3.73 from Rasch model as well as IBM Statistical Package for Social Science (SPSS) version 23. The result from Rasch model analysis showed that majority of the students experienced a moderate level of anxiety in speaking Arabic language, and the personal reason is the most potential source of their anxiety. The independent sample t-test result revealed that the female students were more anxious than the male students while speaking. The Spearman’s rho test result indicated that there was negative significant correlation between students’ anxiety in speaking Arabic language with their acedemic achievement.